Governing urban development in the Low Countries: From managerialism to entrepreneurialism and financialization. (October 2019) - Van Loon, Jannes; Oosterlynck, Stijn; Aalbers, Manuel B
Has the post-war managerial approach to urban governance in the Netherlands and Flanders been replaced by more entrepreneurial and financialized forms? In this paper, we study the transformation of urban governance in the Low Countries through city case studies of Apeldoorn (Netherlands) and Antwerp (Belgium). We show how Dutch urban governance is financialized by connecting local public finance with financialized real estate markets through municipal land banks. However, inter-municipal financial solidarity and ring-fencing municipalities from financial markets create specific continental European processes of financialization. Flemish municipalities, in contrast, have shifted from a model of laissez-faire urban development (embedded in a system of large municipal autonomy) towards entrepreneurial urban growth regimes, in which technocratic public and private actors have increased access to public financial resources, which are used to create large urban renewal projects. In Belgium, autonomous municipal real estate corporations are a crucial instrument for connecting municipal finance to the real estate market.